Analisis Metode Elemen Hingga Pada Kolom Komposit, Sambungan Baja dan Keruntuhan Progresif - Anwar, Anwar; Rahmadani (Journal of Infrastructure and Construction Technology, 2025)
Finite Element Method (FEM) serves as a critical numerical tool for analyzing complex composite and steel structures. This article aims to evaluate the versatility and accuracy of FEM in predicting structural behavior across diverse applications. The study reviews three specific cases: reinforced concrete encased steel columns, haunched gusset plate connections in cold-formed steel, and a mixed element method for progressive collapse analysis. Numerical simulations were validated against experimental data to assess damage mechanisms, ductility, and energy dissipation. The results demonstrate a 42% improvement in lateral capacity for composite structures and a prediction deviation of 25-29% in cold-formed steel connections. Furthermore, the mixed element method exhibited high precision with less than 2% deviation in dynamic analyses. These findings confirm FEM's reliability in optimizing structural design and developing adaptive methods for failure prediction.